Key events in central banking 1609-2001 (London : Central Banking Publications, 2001)
While the choice of any specific year is marking the beginning of the development of Central Banking is to some extent arbitrary, we choose 1609, which saw the first issue of bank notes by a public bank.
oif 09/11/15
Loan
Keywords: Central banking; Banks and banking - central